Growth hormone promotes motor function after experimental stroke and enhances recovery-promoting mechanisms within the peri-infarct area - Sanchez-Bezanilla, Sonia (2021)
Motor impairment is the most common and widely recognised clinical outcome after stroke. Current clinical practice in stroke rehabilitation focuses mainly on physical therapy, with no pharmacological intervention approved to facilitate functional recovery. Several studies have documented positive effects of growth hormone (GH) on cognitive function after stroke, but surprisingly, the effects on motor function remain unclear. In this study, photothrombotic occlusion targeting the motor and sensory cortex was induced in adult male mice. Two days post-stroke, mice were administered with recombinant human GH or saline, continuing for 28 days, followed by evaluation of motor function. Three days after initiation of the treatment, bromodeoxyuridine was administered for subsequent assessment of cell proliferation. Known neurorestorative processes within the peri-infarct area were evaluated by histological and biochemical analyses at 30 days post-stroke. This study demonstrated that GH treatment improves motor function after stroke by 50%-60%, as assessed using the cylinder and grid walk tests. Furthermore, the observed functional improvements occurred in parallel with a reduction in brain tissue loss, as well as increased cell proliferation, neurogenesis, increased synaptic plasticity and angiogenesis within the peri-infarct area. These findings provide new evidence about the potential therapeutic effects of GH in stroke recovery.